(untitled) (University of Denver Undergraduate Research Journal, 2021)
Terrorist attacks often dominate news cycles as reporters seek to interpret the attack through their own desired framing tools. Since “humans are predisposed to attend to negative and threatening information” (Sui et al., 2017), news coverage of terrorist attacks receive a lot of attention thus, how the attack is framed can manipulate the narrative portrayed to the public. This study utilized the Nexus database to examine framing techniques used by a local and an international newspaper in reporting on the Atlanta Centennial Olympic Park bombings both before and after a subject was identified by the FBI. This paper explores how perpetrator identity, legitimacy in sources, and perceived future threats effected how the bombing was covered. Overall, once a suspect had been named, both news outlets utilized “othering” techniques to deemphasize the domestic terrorism label, the sources used became less qualified, and they stopped speculating about the possibility of another attack.